Caracterização do limiar de dor e presença de pontos gatilho de dor em crianças típicas: comparação com adultos saudáveis - Sacramento, Luciane da Silva (Universidade Federal de São Carlos, 2014)
Myofascial pain, represented by points miofascias trigger (MTrPs), has a high prevalence in healthy adults. However, in the case of children, it is not known very well for its occurrence, and even if she is related to dominance and the sensitivity of these individuals before external stimuli, as occurs in pain assessed by pressure pain threshold (PPT). The objectives of this study were to identify the possible presence of MTrPs in typical children featuring their PPTs in the scapular region, and to verify the relationship between the two variables (MTrPs and PPTs). These results were obtained from healthy adults were also compared. Were selected 35 adults (14 men and 21 women; 23, 43 ± 3.42 years; 1.70 ± 0.10 m; 62.90 ± 10.98 kg) and 35 children (15 boys and 20 girls; 9.14 ± 1.68 years; 1.38 ± 0.10 m; 32.41 ± 7.02 kg), with no history of shoulder pathology or cervical spine. All participants underwent investigation with respect to the presence of MTrPs the shoulder musculature and evaluation of the PPT in the regions of neck, shoulder and anterior tibial, by the standards validated in the literature.The X² test was used to compare the distribution of each muscle in latent trigger points (latent TrPs) between groups. After the analysis of normality, parametric tests (test - Student's t for paired and unpaired) and nonparametric (U-Mann Whitney and Wilcoxon tests) were used to compare the amount of PPTs and latent TrPs between groups and sides. Children showed fewer latent TrPs (0.94 ± 1.34) than adults (2.02 ± 2.18). The upper trapezius muscle was more affected by MTrPs reaching 13 adults on the dominant side. The children had lower PPTs compared to healthy adults (P< 0.05). All PPTs correlated with each other in both groups moderately/high. Only adults showed correlations between the amount of latent TrPs and on both sides in total and PPTs. It is concluded that typical children have fewer and smaller latent TrPs and PPTs compared to healthy adults demonstrated to be more sensitive to pain. The pressure sensitive shoulder correlates with the presence of latent TrPs in asymptomatic adults, in other words, children PPTs are associated with increased presence of latent TrPs pattern lacking in children.
Keywords: Fisioterapia; Crianças; Limiar de dor; Pontos gatilho; Child; Pain threshold; Trigger points; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL